THE EVALUATION OF PHYSICAL CONDITION OF MALE AND FEMALE SPRINT ATHLETES IN SEA GAMES 2011 (Arena, 2014)
ABSTRACT The physical abilities, technique mastery, and endurance of a sprinter are very important. To have such important mastery, a sprinter is obliged to have a good physical condition. In a competition, a sprinterâs physical condition must be good so that the performance will be stable and the target can be achieved. Based on that background, this study was aimed to find out the physical condition and achievements of the sprint athletes, both female and male in Sea Games 2011. This research is a quantitative research that uses descriptive analysis method, while the data collection method was done by using secondary data. The samples of this study were all sprint athletes, males and females, who joined the competition in Sea Games 2011. The samples consisted of 7 female athletes and 4 male athletes, so the total samples were 11 athletes. A measurement analysis was conducted through physical condition tests; height and weight, blood pressure, resting, fat thickness, the speed of reaction anticipation, agility, flexibility, balance, back muscle extensor power, leg muscle extensor power, arm muscle power, shoulder muscle power, muscle endurance, abdominal muscle endurance, legs power, Vo2Max endurance, and recovery. The results of this study shows that the physical conditions of the athletes were good. It could be seen through the whole tests and the achievements that were accomplished. It was also perceived through the medals accomplishement by the athletes from East Java. Based on the result of the whole tests that had been conducted, the physical conditions of male and female sprint athletes were good. Thus, it could be concluded that the achievements of male and female sprint athletes in Sea Games 2011 were good. Keywords: Physical Condition, Sprinter, Sea Games 2011.